Role of brassinolide and spraying stages in Zea mays plant - M. Habeeb , Ahmed J.; H. Al-Hilfy, Intsar H. (Innovaciencia, 2018)
Introduction: A Field experiment was conducted at the experimental farm, Dept. of Field Crop (Al-Jadriya), Coll. of Agric., Univ. of Baghdad to study the effects of brassinolide concentrations and spraying stages on yield and its components of maize (Baghdad 3 cultivar) during spring and autumn seasons in 2017. Materials and Methods: A randomized complete blocks design arranged in actorial experiment was used with three replicates. The first factor included three concentrations (0, 2 and 4 mg L-1) of brassinolide,and the second factor included spraying stages (4, 8, 12, 4 + 8, 4 + 12, and 8 + 12 leaves) using the same concentrations for each stage. Results and discussion: Results showed that the concentration 4 mg L-1 gave the highest grain yield (6.59 and 7.15 t ha-1) for its superiority in 500 grain weight (102.74 and 112.26 g) and number of ears per plant (1.43 and 1.44 ear) for both spring and autumn seasons, respectively. The spraying stage (4 + 8 leaves) recorded highest grain yield (6.33 and 6.77 t ha-1), and 500 grain weight (104.73 and 119.20 g) for both spring and autumn seasons, respectively. The effect of interaction for both factors was significant in most studied traits. Conclusion: Therefore, we recommend spraying Brassinolide in a concentration of 4 mg L-1 at the stage 4 + 8 leaves to increase grain yield of maize
Keywords: Maize; Brassinolide; concentration; spraying, stage.